2017
DOI: 10.11594/jtls.07.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Dengue Hemorrhagic Fever (DHF) Associated with the Aedes aegypti Larvae Presence based on the Type of Water Source

Abstract: Aedes aegypti as the vector of Dengue Hemorrhagic Fever (DHF) disease likes to breed in the water containers. The larvae of A. aegypti mostly found in the bath water containers. The presence of A. aegypti larvae could be caused by the type of water source, the container's color, material, location, lid existence and the container's drain frequency. This study aimed to determine the association of water source type with larvae presence and the additional factors. This study used observational analytic with case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…10-12, Moreover, Baharuddin and Rahman 22 found that Ae. aegypti larvae were mostly obtained in plastic containers such as plastic barrels and used rubber tires 18 . It suggested that Ae.…”
Section: Resultsmentioning
confidence: 99%
“…10-12, Moreover, Baharuddin and Rahman 22 found that Ae. aegypti larvae were mostly obtained in plastic containers such as plastic barrels and used rubber tires 18 . It suggested that Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Bio-physicochemical markers of breeding water were categorized based on previous research. The larvae presence categories were defined as in Hidayah's research [13], that is, as "found" and "not found", or "present" and "absent".…”
Section: Methodsmentioning
confidence: 99%
“…aegypti dapat ditemukan pada tempat-tempat penyimpanan air di dalam rumah. 7 Adapun Ae. albopictus banyak ditemukan di luar rumah seperti di area pekarangan yang penuh vegetasi yang tidak dikelola dengan baik.…”
Section: Pendahuluanunclassified